2000
DOI: 10.1097/00000539-200002000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Oral Ketamine/Midazolam Is Superior to Intramuscular Meperidine, Promethazine, and Chlorpromazine for Pediatric Cardiac Catheterization

Abstract: Oral medication can be superior to IM injections for sedating children with congenital heart disease; however, the safety of all medications remains an issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
0
17
0
3
Order By: Relevance
“…It can be used intramuscular (IM) in a dose of 3 to 8 mg/kg 6 IV with a bolus of 1 mg/kg, followed by a continuous infusion of 50 to 70 mcg/kg/min 7 or orally with or without midazolam in a dose of 10 mg/kg. 8 Ketamine should be combined with an antisialagogue to prevent hypersalivation and airway irritability. Glycopyrrolate 0.005 mg/kg IM or IV should be added.…”
Section: Sedation Techniquesmentioning
confidence: 99%
“…It can be used intramuscular (IM) in a dose of 3 to 8 mg/kg 6 IV with a bolus of 1 mg/kg, followed by a continuous infusion of 50 to 70 mcg/kg/min 7 or orally with or without midazolam in a dose of 10 mg/kg. 8 Ketamine should be combined with an antisialagogue to prevent hypersalivation and airway irritability. Glycopyrrolate 0.005 mg/kg IM or IV should be added.…”
Section: Sedation Techniquesmentioning
confidence: 99%
“…Nevertheless, even in these centres, some procedures are performed in the presence of anaesthesiologists, and the question always remains how the decision to proceed with or without an anaesthesiologist is taken. Although, in close collaboration with anaesthesia services, an algorithm to administer sedation in a catheterization laboratory can be developed, there will still be the need for skilled personnel in the case of an emergency [23][24][25]. More importantly, the concept of conscious sedation in young children could be synonymous with unmonitored general anaesthesia.…”
Section: Anaesthesiologist Versus Nonanaesthesiologistmentioning
confidence: 99%
“…Qp:Qs decreased in patients with cardiac shunt, which lead to further desaturation in patients with cyanotic heart disease (Qp:Qs < 1).31 In another study on pediatric patients undergoing elective catheterization, it was shown that propofol anesthesia is a practical alternative to ketamine because of the significantly shorter recovery time. 30 Narcotic Anesthesia…”
Section: Ketaminementioning
confidence: 99%